2010
DOI: 10.1249/mss.0b013e3181e1fba9
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in US Youth

Abstract: Purpose To describe physical activity (PA) levels by race/ethnicity, age, gender, and weight status in a representative sample of U.S. youth. Methods Cross-sectional data from the 2003–4 and 2005–6 National Health and Nutrition Examination Survey (NHANES) were combined and analyzed. Youth ages 6 to 19 with at least 4 10-hour days of PA measured by accelerometry were included (N=3,106). Outcomes included mean counts per minute and minutes spent in moderate to vigorous PA (MVPA). Results 6 to 11 year olds sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
153
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 292 publications
(172 citation statements)
references
References 42 publications
19
153
0
Order By: Relevance
“…This finding reflected an earlier report which suggested that less than one half of American children (6-11) regularly participate in vigorous physical activity and obtain the recommended 60 min per day of physical activity; only 8% of adolescents achieve this goal (Troiano et al, 2008). These figures vary across all demographic variables such as gender, SES, and race, to name but a few (Belcher et al, 2010). Within physical education itself, Smith, Lounsbery, and McKenzie (2014) list a number of studies that have examined physical activity within elementary and middle schools.…”
Section: Published Researchsupporting
confidence: 76%
“…This finding reflected an earlier report which suggested that less than one half of American children (6-11) regularly participate in vigorous physical activity and obtain the recommended 60 min per day of physical activity; only 8% of adolescents achieve this goal (Troiano et al, 2008). These figures vary across all demographic variables such as gender, SES, and race, to name but a few (Belcher et al, 2010). Within physical education itself, Smith, Lounsbery, and McKenzie (2014) list a number of studies that have examined physical activity within elementary and middle schools.…”
Section: Published Researchsupporting
confidence: 76%
“…[19,20] Specifically, research has demonstrated a decline in PA levels with age, particularly in adolescent females. [21,22] The current study shows that PA levels declined at an earlier age in females compared with males (10 years v. 13 years).…”
Section: Researchmentioning
confidence: 99%
“…In addition, secondary data sources, the 2009-10 Health-Behavior in School-Aged Children Survey and 2003-06 NHANES, identified differences in the results by sex, age, and ethnicity, with males, younger children, and nonwhite ethnicities being more active than their female, older, and white counterparts. 15,25 Sedentary Behaviors: D…”
Section: Overall Physical Activity: D-mentioning
confidence: 99%
“…39 Operationally, sedentary behavior has been defined as the amount of time spent at low activity counts on an accelerometer, such as < 100 counts/min. 40 Estimates from NHANES 15 accelerometry data indicated that American children and youth spend over 7 hours being sedentary, and children spend more time being sedentary as they get older. Given the lack of a specific guideline for overall sedentary behavior, the Report Card Research Advisory Committee used total screen time as the primary indicator.…”
Section: Sedentary Behaviorsmentioning
confidence: 99%